2012
DOI: 10.1007/s10561-011-9291-z
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of predisposing factors for contamination of bone and tendon allografts

Abstract: Bone and tissue allografts are widely used in transplantation. The increasing demand for safe allografts must be met, while minimizing disease transmission. We analysed the incidence and potential risk factors of allograft contamination and the effectiveness of disinfection, by reviewing 22 years of tissue bank activity and 474 donor procurements. We also compared different disinfection procedures used over the 22 years. The overall contamination rate was 10.1%. Risk factors were related to the donor or procur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
20
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 32 publications
3
20
0
Order By: Relevance
“…A number of studies performed tests on tissues that were contaminated by researchers following recovery to assess the efficacy of their decontamination methods. Similar to the recovered contaminating microorganisms observed in Schubert et al (2012), the most commonly inoculated organisms in these studies were Staphylococci and Bacillus species. Seven studies sought to test various decontamination methods on tissues infected with viruses, such as HIV2, pseudorabies virus (PRV), bovine virus diarrhoea virus (BVD), hepatitis A virus (HAV), and porcine parvovirus (PPV).…”
Section: Resultssupporting
confidence: 85%
See 4 more Smart Citations
“…A number of studies performed tests on tissues that were contaminated by researchers following recovery to assess the efficacy of their decontamination methods. Similar to the recovered contaminating microorganisms observed in Schubert et al (2012), the most commonly inoculated organisms in these studies were Staphylococci and Bacillus species. Seven studies sought to test various decontamination methods on tissues infected with viruses, such as HIV2, pseudorabies virus (PRV), bovine virus diarrhoea virus (BVD), hepatitis A virus (HAV), and porcine parvovirus (PPV).…”
Section: Resultssupporting
confidence: 85%
“…In Schubert et al (2012), the presence of a number of contaminating bacteria and fungi were observed. These included species, in descending order of prevalence, such as coagulase negative Staphylococcus , Micrococcus , Bacillus cereus , Corynebacterium , Penicilium , Alcaligenes , Lactobacillus , Eschericcia coli , Acinetobacter , Enterococcus , Pseudomonas aeruginosa , Pneumococcus , and the fungus, Candida.…”
Section: Resultsmentioning
confidence: 96%
See 3 more Smart Citations